Technical, Scale, and Allocative Efficiencies in U.S. Banking: An Empirical Investigation - Aly, Hassan Y.; Grabowski, Richard; Pasurka, Carl; Rangan, Nanda (The Review of Economics and Statistics, 1990)
A nonparametric frontier approach is used to calculate the overall, technical, pure technical, allocative, and scale efficiencies for a sample of 322 independent banks. The sample was drawn from the Federal Deposit Insurance Corporation tapes on the Reports of Conditions and Reports of Income (Call Reports) for the year 1986. The results indicate a low level of overall efficiency. The main source of inefficiency is technical in nature, rather than allocative. Separate efficiency frontiers are constructed to test the effect of branching. However, the distributions of efficiency measures for branching and nonbranching banks are not found to be different. Coauthors are Richard Grabowski, Carl Pasurka, and Nanda Rangan. Copyright 1990 by MIT Press.